Pengembangan Ketrampilan Service Konsumen Dan Daya Tarik Desain Iklan Pada Pedagang Kuliner Kota Boyolali - Firdaus Azwar Ersyad; Tika Ristia Djaya; Edi Nurwahyu Juliyanto (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Implementing this community activity aims to develop the skills of culinary traders in Boyolali in increasing Excellent Service. The team uses a simulation method of providing excellent service practice and exposure to the use of the CorelDraw application. With this method, the skills of the traders will be seen in providing excellent service to consumers. With advertising design training using the CorelDraw application, traders are more skilled in designing which is useful for showing aesthetics and introducing the public to their products to make them look attractive, so as to increase sales turnover. This activity will be held on Jln. Pandanaran 405 Winong Hamlet, Boyolali District, Boyolali Regency, Central Java